2011
DOI: 10.1063/1.3593006
|View full text |Cite
|
Sign up to set email alerts
|

High electron mobility transistors on plastic flexible substrates

Abstract: The double-flip transfer of indium phosphide ͑InP͒ based transistors onto plastic flexible substrates was demonstrated. Modulation doped field effect transistor layers, epitaxially grown on InP bulk substrates, were transferred onto sapphire using a masked ion-cutting process. Following layer transfer, transistors were fabricated at low temperatures ͑Յ150°C͒. The device structure was then bonded to flexible substrate, and laser ablation was used to separate the initial bond. The transferred transistors were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…6 In order to reach better electrical performance, the use of InAlAs/InGaAs high electron mobility transistor (HEMT) integrated into the polyimide substrate (Kapton) and embedded into thin-film micro-strip (TFMS) lines, is proposed in this letter. It is to be noted that only one paper dealing with the fabrication process of large 50 lmgate InGaAs/InAlAs HEMT on flexible substrate (HEMT-FS) 7 has been published. If the electrical static performance was reported, dynamic performance was missing, which is among the main objective of this letter.…”
mentioning
confidence: 99%
“…6 In order to reach better electrical performance, the use of InAlAs/InGaAs high electron mobility transistor (HEMT) integrated into the polyimide substrate (Kapton) and embedded into thin-film micro-strip (TFMS) lines, is proposed in this letter. It is to be noted that only one paper dealing with the fabrication process of large 50 lmgate InGaAs/InAlAs HEMT on flexible substrate (HEMT-FS) 7 has been published. If the electrical static performance was reported, dynamic performance was missing, which is among the main objective of this letter.…”
mentioning
confidence: 99%
“…Recently, InGaAs NMs were developed for applications in optoelectronic devices, such as PDs, 83,84 LEDs, 85 and field effect transistors. 86 For example, D. Fan et al demonstrated a thinfilm InGaAs p-i-n PD array fabricated on a thin and flexible polyimide Kapton substrate.…”
Section: Applications Of Ingaas Nanomembranesmentioning
confidence: 99%